Climate change of the temperature component and its impact on tomato yield in Anbar Governorate - Al-Dulaimi, Mohammad Rahim; Al-Janabi, Hamid Rajab (Al-Adab Journal, 2021)
The study dealt with climatic changes of the temperature component and its impact on the productivity of the tomato crop in Anbar Governorate. The study focused on a very important problem facing the agricultural sector, which is (climate change), which represents the most important factor in agricultural production, as the exacerbation of this problem contributed to the shortening of the period of crop growth and productivity Because the rise in temperatures above 48 ° C contributes to the cessation of the physiological processes of the crop, as the rate of evaporation / transpiration increases, and consequently the production processes stop, and then the death of the seedlings, and then the plant withering and then its death gradually and rapidly The study found: -- The annual rates of change in the normal temperatures of the stations of the study area reached the highest amount of change in Al-Rutba station by (1.42) and the lowest rate of change was recorded in Al-Ramadi station by (1.15).- The rate of change of yield per dunum of tomato yield reached in Anah district (1.04) tons per dunum, in the districts of Hadith and Al-Qaim (1.14) tons per dunum, in Heet district (1.1) tons per dunum, and in Ramadi district (1.08) tons per dunum.